2020
DOI: 10.3892/etm.2020.8649
|View full text |Cite
|
Sign up to set email alerts
|

Naringin inhibits colorectal cancer cell growth by repressing the PI3K/AKT/mTOR signaling pathway

Abstract: In recent years, the incidence of colorectal cancer (CRC) has increased and research into new treatment methods for CRC has become a hot topic. Naringin has an inhibitory effect on the PI3k/AKT/mTOR signaling pathway in various tumor cell types and the effect of naringin is closely related to the occurrence and proliferation of tumor cells. The aim of this present study was to investigate whether naringin could inhibit the proliferation of CRC cells by inhibiting the PI3K/AKT/mTOR signaling pathway. This could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 36 publications
(42 reference statements)
0
41
0
Order By: Relevance
“…mTOR is the key regulator of autophagy in cancer cells. Naringin promoted apoptosis of colorectal cancer by inhibiting the PI3K/AKT/ mTOR signaling pathway (Cheng et al, 2020). Naringin improves the function of HUVECs under high glucose stress through activation of the PI3K-Akt-mTOR pathway to inhibit autophagy (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…mTOR is the key regulator of autophagy in cancer cells. Naringin promoted apoptosis of colorectal cancer by inhibiting the PI3K/AKT/ mTOR signaling pathway (Cheng et al, 2020). Naringin improves the function of HUVECs under high glucose stress through activation of the PI3K-Akt-mTOR pathway to inhibit autophagy (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that naringin has antineoplastic activities and treatment with naringin can reduce proliferation, and viability, while also enhancing apoptosis in HT-29 colon adenocarcinoma ( Elansary et al, 2020 ) and CT26 colorectal cancer cell lines ( Zhou et al, 2018 ). Another study indicated that treatment of human colon tumor cell lines (HCT116 and SW620) with naringin suppressed the CRC cell viability and proliferation, and promoted apoptosis by suppressing the phosphoinositide-3 kinase (PI3K)/protein kinase-B (also known as Akt)/mammalian target of rapamycin (mTOR) signaling pathway ( Chidambara Murthy et al, 2012 ; Cheng et al, 2020 ). Naringin treatment also induced apoptosis in Colo 205 and Colo 320 human colon cancer cells ( Ugocsai et al, 2005 ).…”
Section: Anticancer Activities Of Naringinmentioning
confidence: 99%
“…Previous studies have identified anti-cancer drugs inducing apoptosis by blocking the PI3K/AKT signaling pathway (41,42). In colorectal cancer, Nar inhibits cell growth and induces apoptosis via blocking the PI3K/AKT signaling pathway (15). By targeting this pathway, Nar inhibits the proliferation of thyroid cancer cells and induces apoptosis (43).…”
Section: Discussionmentioning
confidence: 99%
“…then inhibiting cancer cell proliferation and inducing cancer cell apoptosis (12)(13)(14). Nar can induce apoptosis and inhibit cancer cell growth in colorectal cancer, cervical cancer, ovarian cancer, liver cancer and other types of cancer (15)(16)(17)(18). However, the effect of Nar on gastric cancer SNU-1 cells and its mechanism remain unclear.…”
Section: Naringin Induces Apoptosis Of Gastric Carcinoma Cells Via Blocking the Pi3k/akt Pathway And Activating Pro-death Autophagymentioning
confidence: 99%